Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen pada Katorroan Cafe Batutumonga Kabupaten Toraja Utara - Citra Tiku Datu Batara; Ade Lisa Matasik; Abedneigo C. Rambulangi (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study aims to analyze the influence of service quality on consumer satisfaction at Katorroan Cafe Batutumonga, North Toraja Regency. This research uses a quantitative associative method with a questionnaire as a data collection tool involving 60 respondents who are visitors to the cafe. Data analysis was carried out using descriptive analysis, validity test, reliability test, classical assumption test, simple linear regression analysis, and hypothesis testing (t-test). The results showed that the service quality at Katorroan Cafe Batutumonga was in the good category, and consumer satisfaction was in the satisfied category. However, the results of the simple linear regression test showed a negative and significant influence of service quality on consumer satisfaction with a regression coefficient of -0.404 and a significance value of 0.000. This indicates that an increase in service quality is paradoxically followed by a decrease in consumer satisfaction in the context of this study. The coefficient of determination (R²) is 0.195, meaning that service quality contributes 19.5% to consumer satisfaction, while the remaining 80.5% is influenced by other factors outside the study.